2022
DOI: 10.3390/ijerph19031448
|View full text |Cite
|
Sign up to set email alerts
|

“Green Enough Ain’t Good Enough:” Public Perceptions and Emotions Related to Green Infrastructure in Environmental Justice Communities

Abstract: The concept of biophilic urban planning has inspired neighborhood greening projects in many older urban communities in the USA and beyond. The strengths (e.g., environmental management, biodiversity, heat island mitigation) and challenges (e.g., greenwashing, green gentrification) of such projects are well-documented. Additional research on the relationship between these projects and various social factors (e.g., public perceptions, feelings, and mental health and well-being) is necessary to better understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Overcoming the previous lack of knowledge of the presence of pollution or its harmful effects, current residents are realizing the extent of the continuous exposure to pollutants and how that exposure has affected their health and daily quality of life. This awareness reflects current trends in environmental justice research [ 4 ], as well as known environmental racial disparities in the southeastern US region [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 69%
“…Overcoming the previous lack of knowledge of the presence of pollution or its harmful effects, current residents are realizing the extent of the continuous exposure to pollutants and how that exposure has affected their health and daily quality of life. This awareness reflects current trends in environmental justice research [ 4 ], as well as known environmental racial disparities in the southeastern US region [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 69%
“…For example, Meenar et al. (2022) conducted semi‐structured interviews of community residents regarding green infrastructure in Camden, New Jersey, and found that green infrastructure projects do not automatically guarantee environmental justice and health equity. Green infrastructure redevelopment projects can also have adverse social impacts.…”
Section: Equity and Swm Servicesmentioning
confidence: 99%
“…Additionally, several studies have explored communities’ perceptions on environmental concerns, such as air quality (e.g. Brody et al , 2004; Meenar, Heckert and Adlakha, 2022), water quality (e.g. Stedman and Hammer, 2006), toxic chemicals (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%